1962
DOI: 10.1182/blood.v19.3.349.349
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Cell Proliferation in Cultures of Human Peripheral Blood

Abstract: The kinetics of growth of peripheral blood cells in tissue culture are described. There was a rapid increase of cells in DNA synthesis beginning at 24 hours and by 72 hours 40-45 per cent of the cells were in DNA synthesis. Mitotic rates of ∼ 1 per cent/hour were seen after 72 hours in cultures. Studies with tritiated thymidine and colchicine indicated that these cells represent transformed lymphocytes and do not arise from the cells in DNA synthesis at time zero or from any other small population of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

1963
1963
1976
1976

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(32 citation statements)
references
References 2 publications
4
28
0
Order By: Relevance
“…It has been cautiously suggested that the transformation of the small lymphocyte is an antigen-antibody-like reaction to PHA (Mackinney et al, 1962;Elves and Wilkinson, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…It has been cautiously suggested that the transformation of the small lymphocyte is an antigen-antibody-like reaction to PHA (Mackinney et al, 1962;Elves and Wilkinson, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Small lymphocytes from peripheral blood have been cultured, and with the aid of phytohemagglutinin (Hungerford et al, 1959;Nowell, 1960) have been shown to enlarge and undergo mitosis in the course of 24-30 hr. (Carstairs, 1962;Porter and Cooper, 1962~;Mackinney et al, 1962;Johnson and Roberts, 1963). Carstairs ( 1962) incubated blood with colloidal iron first of all, and then centrifuged to remove the phagocytic cells, including the monocytes, which had become heavier after ingesting the iron.…”
Section: The Lymphocyte-production Pathwaymentioning
confidence: 99%
“…A few days after phytohemagglutinin (PHA)$, or other mitogens, are added to cultures of peripheral blood lymphocytes of patients affected by chronic lymphatic leukemia (CLL) DNA synthesis and cell division occurs. However, compared to the response of normal lymphocytes, these events are impaired (Havemann & Rubin, 1968 ;MacKinney, Stohlman & Brecher, 1962;Nowell, 1960;Oppenheim, Whang & Frei, 1965;Quaglino & Cowling, 1964;Robbins, 1964;Rubin, Havemann & Dameshek, 1969;Schrek & Rabinowitz, 1963).…”
Section: Introductionmentioning
confidence: 99%